Astaxanthin Modulation of Signaling Pathways That Regulate Autophagy - Kim, Suhn Hyung (Mar Drugs, 2019)
Autophagy is a lysosomal pathway that degrades and recycles unused or dysfunctional cell components as well as toxic cytosolic materials. Basal autophagy favors cell survival. However, the aberrant regulation of autophagy can promote pathological conditions. The autophagy pathway is regulated by several cell-stress and cell-survival signaling pathways that can be targeted for the purpose of disease control. In experimental models of disease, the carotenoid astaxanthin has been shown to modulate autophagy by regulating signaling pathways, including the AMP-activated protein kinase (AMPK), cellular homolog of murine thymoma virus akt8 oncogene (Akt), and mitogen-activated protein kinase (MAPK), such as c-Jun N-terminal kinase (JNK) and p38. Astaxanthin is a promising therapeutic agent for the treatment of a wide variety of diseases by regulating autophagy.